2003
DOI: 10.1037/0012-1649.39.2.349
|View full text |Cite
|
Sign up to set email alerts
|

A biopsychosocial model of the development of chronic conduct problems in adolescence.

Abstract: A biopsychosocial model of the development of adolescent chronic conduct problems is presented and supported through a review of empirical findings. This model posits that biological dispositions and sociocultural contexts place certain children at risk in early life but that life experiences with parents, peers, and social institutions increment and mediate this risk. A transactional developmental model is best equipped to describe the emergence of chronic antisocial behavior across time. Reciprocal influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
815
1
37

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 963 publications
(896 citation statements)
references
References 233 publications
(281 reference statements)
43
815
1
37
Order By: Relevance
“…Theoretical models of the development of antisocial behavior have embraced this equifinality, acknowledging the numerous ways in which different loci of risk can interact to promote habitual antisocial responses (Dodge and Pettit 2003;Frick and Morris 2004;Guerra and Huesmann 2004). Contemporary strategies for the assessment of youths' violent and nonviolent antisocial behavior involve multiple methods and multiple informants to ensure that the full spectrum of risk is covered (Borum and Verhaagen 2006;McMahon and Frick 2005).…”
Section: Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical models of the development of antisocial behavior have embraced this equifinality, acknowledging the numerous ways in which different loci of risk can interact to promote habitual antisocial responses (Dodge and Pettit 2003;Frick and Morris 2004;Guerra and Huesmann 2004). Contemporary strategies for the assessment of youths' violent and nonviolent antisocial behavior involve multiple methods and multiple informants to ensure that the full spectrum of risk is covered (Borum and Verhaagen 2006;McMahon and Frick 2005).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Additional identified risk factors include academic difficulties (e.g., low intelligence, poor achievement, learning disability; Huesmann et al 1987;Stipek 1998); psychopathic tendencies or callousness-unemotionality (e.g., shallow affect, lack of concern for others; Frick et al 2003); and psychopathology or related emotional problems (e.g., depression, psychotic symptoms; Boxer 2007; Knox et al 2000). This is not an exhaustive list of risk factors for aggression, but these are some of the key influences often implicated in models of aggression development (Dodge and Pettit 2003;Frick and Morris 2004;Guerra and Huesmann 2004) and highlighted in recommendations for the general assessment and treatment of aggression and antisocial behavior as well as risk for violence (Borum and Verhaagen 2006;Boxer and Frick 2008;Hoge et al 2008).…”
mentioning
confidence: 99%
“…We would expect these youths to be especially likely to be characterized by callous-unemotional traits (Zych, Ttofi, & Farrington, 2016) and to hold positive expectations for the outcomes associated with aggressive behavior (Schwartz et al 1998). The pathways from early aggression to later antisocial outcomes are likely to be influenced by interactive and transactional processes (Dodge and Pettit 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it remains unclear whether the APSD has predictive utility above and beyond a broader array of risk factors for violent and antisocial behavior. For instance, several review articles have indicated that neuropsychological deficits, peer rejection, family dysfunction, and neighborhood disorganization are important predictors of youth offending (Dodge & Pettit, 2003;Loeber & Farrington, 2000). Future studies should be conducted to examine whether the APSD adds incrementally to the prediction of antisocial behavior once these other variables are considered.…”
Section: Discussionmentioning
confidence: 99%